Genetics of female infertility: Molecular study of newborn ovary homeobox gene in poor ovarian responders - Osamah Batiha; Nour Alhoda Alahmad; Amer Sindiani; Khaldon Bodoor; Sherin Shaaban; Mohammad Al-Smadi (Wolters Kluwer Medknow Publications, 2019)
Background: Newborn ovary homeobox (NOBOX) gene plays a critical role in the transcriptional regulation of oocyte-specific genes. Previous studies have demonstrated a pathogenic effect of NOBOX variants on premature ovarian insufficiency (POI) patients. Poor ovarian response (POR) is a risk factor for POI. Therefore, genetic variants in the NOBOX gene may also be studied as risk factors for POR development. Aims: The aim of the study is to investigate the association between seven known NOBOX single-nucleotide polymorphisms (SNPs) and POR in Jordanian females. Settings and Design: This was a case-control study of 60 females with POR for controlled ovarian hyperstimulation and 59 healthy females with no history of reproductive problems. Blood samples were collected from the participants and seven SNPs of NOBOX gene were screened. Subjects and Methods: DNA was extracted from blood samples. Polymerase chain reaction with primers specific for seven known SNPs in NOBOX gene was used to amplify the specified region within the gene followed by Sanger sequencing. Results: The seven SNPs investigated in this study, namely, rs77587352 (c.271G>T, p. Gly91Trp), rs7800847 (c.349C>T, p. Arg117Trp), rs193303102 (c.907C>T, p. Arg303X), rs193303103 (c.1025G>C, p. Ser342Thr), rs193303104 (c.1048G>T, p. Val350Leu), rs201947677 (c.1064G>A, p. Arg355His), and rs146227301 (c.1856C>T, p. Pro619Leu), only represent the wild-type allele in both females with POR and healthy participants. Conclusions: The results show that only monomorphic genotype of the NOBOX variants was found in Jordanian females studied.